Design of Population Information System based on WEB In Pasirkaliki Village, Cimahi City - Minah Jaya, Suhana (Greenation International Journal of Engineering Science, 2023)
Pasirkaliki Village is one of the government agencies located in North Cimahi District, Cimahi City, that requires an information system for the right solution in disseminating information both for the Pasirkaliki community itself and for other wider communities. One of the information that must be conveyed to the Pasirkaliki community is information about population data, especially in terms of the number of residents, number of births, number of deaths, number of residents who moved, number of migrants, and the number of low-income families living in Pasirkaliki sub-district., While the information that can be conveyed to other wider communities is about the number of residents, the number of disadvantaged residents, and data about the population of Pasirkaliki sub- district. The information system in Pasirkaliki Village has been manually, namely through handwriting, and stored in a book so that it has the risk of being lost, forgotten, and damaged. Data handling like this makes the level of data security less, and time processing data are inefficient. With the information system, it will make it easier for village employees to store population data so that existing risks can be minimized. And with a population information system, Pasirkaliki Village can convey information about population data to the community and agencies that need it.